Self microemulsifying powder using Aerosil as a carrier - Arju, N; Bara, PK; Amin, MT; Bhowmik, DR; Hossain, MS (Bangladesh Journal of Scientific and Industrial Research, 2021)
This investigation highlighted the development of a solid self micro emulsifying drug delivery system (solid SMEDDS) for improved oral delivery of Valsartan. Liquid SMEDDS were formulated and then the liquid formulation was transformed into free-flowing powder by adsorption on a solid carrier. Here the formulations were prepared in various ratios of the drug to the excipients. Various evaluation studies were performed. In-vitro release profiles of all formulations were evaluated. The concentration of the diffused drug was measured using a UV-visible spectrophotometer at λmax= 250 nm. The faster dissolution was exhibited by the formulations containing Avicel. The experimental results for prepared solid-SMEDDS showed the improved dissolution of the study drug in a short time. F-3 (Assay:77%; Dissolution: 51.7% after 45 min, 63% after 60 min) and F-4 (Assay:63%; Dissolution: 49.1% after 45 min, 67% after 60 min) showed better evaluation study and this two might be formulated in future. Thus, this study revealed the formulation solid-SMEDDS using Aerosil 200 as an adsorbent with the potential of enhancing the solubility, and dissolution rate of the drug. Bangladesh J. Sci. Ind. Res.56(2), 141-146, 2021